A Corpus-Based Study on Modality Markets Expressing Politeness Strategies in American Political Speeches - Võ Thị Thanh Tâm (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
On the basis of the aims set up as presented above, this research made anattempt to accomplish the following objectives:● Classifying and describing types of modality markers used by Americanpoliticians in their political speeches.● Categorizing politeness strategies from modality markers collected fromAmerican political speeches.